2011
DOI: 10.5713/ajas.2011.11227
|View full text |Cite
|
Sign up to set email alerts
|

Body Weight Changes of Laboratory Animals during Transportation

Abstract: The majority of laboratory animals were transported from commercial breeders to a research facility by ground transportation. During the transportation, many biological functions and systems can be affected by stress. In this experiment, the change of body weight during the transportation was measured and the recovery periods from the transportation stress established based on the body weight changes. Total 676 laboratory animals which were aged between 3 to 9 wk old were studied. The transportation time taken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 8 publications
0
9
0
1
Order By: Relevance
“…[ 44 ]. Weight loss, however, was modest compared to other transfer studies [ 13 , 14 , 45 ], a difference that may be due to the fact that total transfer procedures are unlikely to be identical in different studies. The relatively modest weight loss in the present study may be explained by decreased food and water intake and increased defecation during transfer [ 4 , 46 , 47 ], since BW gain returned to control levels within two days.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…[ 44 ]. Weight loss, however, was modest compared to other transfer studies [ 13 , 14 , 45 ], a difference that may be due to the fact that total transfer procedures are unlikely to be identical in different studies. The relatively modest weight loss in the present study may be explained by decreased food and water intake and increased defecation during transfer [ 4 , 46 , 47 ], since BW gain returned to control levels within two days.…”
Section: Discussionmentioning
confidence: 58%
“…The relatively modest weight loss in the present study may be explained by decreased food and water intake and increased defecation during transfer [ 4 , 46 , 47 ], since BW gain returned to control levels within two days. Body weight sometimes is used as guiding indicator for determining the necessary acclimatization period of animals after transfer [ 45 ]. Given, however, the marked differences in body weight changes in response to apparently different overall transfer procedures and, moreover, that body weight seems to stabilize earlier than other parameters, it might not be advisable to rely on this parameter alone.…”
Section: Discussionmentioning
confidence: 99%
“…or differences in individual physiologic variations in response to a stressful situation. As a large degree of variation in other acute physiologic responses to shipping has been demonstrated (Landi et al, 1982 ; Aguila et al, 1988 ; van Ruiven et al, 1998 ; Swallow et al, 2005 ; Capdevila et al, 2007 ; Laroche et al, 2009 ; Shim et al, 2009 ; Arts et al, 2012 ; Lee et al, 2012 ), it is not surprising to see variations in the acute responses of the GM as well.…”
Section: Resultsmentioning
confidence: 99%
“…The transportation of laboratory mice from producers and animal facilities is a common occurrence in research. Most animal distributors take great care in ensuring that proper housing and environmental conditions are maintained throughout the shipping process, but even with strict guidelines to ensure animal welfare, previous studies have shown that the shipping process can induce numerous physiologic changes that are indicative of stress in rodents (Landi et al, 1982 ; Aguila et al, 1988 ; van Ruiven et al, 1998 ; Swallow et al, 2005 ; Capdevila et al, 2007 ; Laroche et al, 2009 ; Shim et al, 2009 ; Arts et al, 2012 ; Lee et al, 2012 ). From an animal welfare standpoint, it is important to recognize that these stress-like responses in animals do not necessarily indicate a pathologic change.…”
Section: Introductionmentioning
confidence: 99%
“…This stress is not confined to the transported animal, but it can also affect their offspring [ 5 , 6 ]. Different parameters have been used to assess stress in animals, such as: cortisol, corticosterone and flucose, food and water consumption and weight loss [ 7 ]. After high stress levels, the mice require much time for the heart rate (HR) and breathing rate (BR) physiological signals to return to values within the normal levels.…”
Section: Introductionmentioning
confidence: 99%